Convergence Patterns and Transition Paths of Alternative and Renewable Energy Consumption across Provincial Clusters in Thailand - Choesawan, Chairat (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This study examines the stochastic conditional convergence of alternative and renewable energy consumption and determines the structural breaks across 18 provincial clusters in Thailand over the period 2001 – 2018, to find out the convergence patterns and the transition paths of the long-term development. The result reveals that there is no convergence characteristic across the entire sample clusters owing to the existence of two breaks. However, alternative and renewable consumption of 18 provincial clusters can be partially merged into three unique sets of equilibrium with the different transition paths as follows: 1) the group with a high level and showing continued growth (power and cogeneration); 2) the group with a medium level and experiencing a sharp decline (heat), and 3) the group with a low level and maintaining a constant (biofuel). In response to renewable development, Thailand should set out identical alternative targets towards the unique distribution characteristics of renewable instead of a common alternative energy policy like AEDP 2015. To enhance the broader cooperation and reduce the dispersion across provincial clusters in the long run, it is necessary to expand the use of solar power and to convert biomass into the cogeneration of heat and power.